Peridynamics analysis of crack propagation in concrete considering random aggregate distribution - Bin Geng; Ze Li; Yigong Zhao; Xiaoyan Zhang (Scientific Reports)
Abstract The mechanical properties and fracture behavior of concrete are controlled by aggregate characteristics, and the distribution of aggregates is uncertain. Traditional studies on concrete crack propagation mainly conduct deterministic analysis based on the position and size of the aggregates, rarely considering the uncertainty of aggregate distribution. Based on the Peridynamics (PD) theory, random distribution functions are introduced to describe the geometric characteristics and positional parameters of concrete aggregates. Simulating the effect of random distribution of aggregates on concrete crack propagation by presetting random aggregates. For the first time, the Boundary Damage Ratio (BDR) is proposed to quantitatively describe the influence of cement mortar and aggregate on crack propagation, revealing the influence rules of random aggregate parameters on concrete damage provides a new method for studying concrete crack propagation. The research results show that the size and position of aggregates determine the crack propagation path during concrete failure. The BDR can indicate the quality of the concrete grading and the intensity of the aggregate’s guiding effect on crack propagation. It was found that the aggregate size and the BDR follow a Weibull distribution; the larger the aggregate size, the smaller the shape parameter.